Cabergoline as an adjuvant to standard heart failure treatment in peripartum cardiomyopathy: A case report and review of the literature - Giuseppe Caruso; Annalisa Scopelliti; Sara Scaramuzzino; Giuseppina Perrone; Paola Galoppi; Innocenza Palaia; Ludovico Muzii; Pierluigi Benedetti Panici; Roberto Brunelli (Elsevier, 2021)
Introduction: Peripartum cardiomyopathy (PPCM) is a rare and idiopathic form of dilated cardiomyopathy presenting late in pregnancy or early postpartum. Since the 16-kDa fragment of prolactin has been identified as a key factor in the pathophysiology of PPCM, prolactin inhibitors have been used as an adjuvant to standard heart failure treatment. Although bromocriptine is the current first choice, promising results have been reported with cabergoline, albeit scant. Case Presentation: We presented the case of a 41-year-old woman who received a diagnosis of PPCM one week after delivery and was successfully treated with cabergoline, finally experiencing a complete recovery. Conclusion: The case adds to the scant evidence supporting the use of cabergoline in PPCM patients. We argue that the favorable pharmacokinetic and metabolic profiles of this drug should prompt its consideration as a valid alternative prolactin inhibitor in these critical patients.